2011
DOI: 10.1002/kin.20550
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of copper(II)‐catalyzed oxidation of S(IV) by atmospheric oxygen in ammonia buffered solutions

Abstract: To understand the chemistry of Cu(II)-NH 3 -S(IV)-O 2 system, the kinetics of the oxidation of sulfur(IV) catalyzed by amminecopper(II) complexes has been studied in the ammonia-buffered solutions. Sulfur(IV) is oxidized to sulfate. The complexes, Cu(NH 3 ) 2+ , Cu(NH 3 ) 2+ 2 , and Cu(NH 3 ) 2+ 3 appear to be equally reactive and Cu(NH 3 ) 2+ 4 appears to be unreactive. The kinetics obey the rate law: 2+ 3 complexes, which appear to be equally reactive. The values of α 1 and γ 1 were found to be (1.32 ± 0.21)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…S(IV), were studied by following the decrease in the concentration of S(IV). This procedure was the same as that described by Brodizinsky et al [42] and subsequently used by us [43][44][45][46]. The reactions were conducted in 0.15 L Erlenmeyer flasks open to air, to allow the passage of atmospheric oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…S(IV), were studied by following the decrease in the concentration of S(IV). This procedure was the same as that described by Brodizinsky et al [42] and subsequently used by us [43][44][45][46]. The reactions were conducted in 0.15 L Erlenmeyer flasks open to air, to allow the passage of atmospheric oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…As reported by Sharma 36 and Mudgal 37 a radical mechanism operates in those reactions in which the inhibition parameter lies the range 10 3 -10 4 . In this study the value of inhibitor parameter is found to be 2.46×10 3 , which lies in the same range.…”
Section: Effect Of Temperaturementioning
confidence: 73%
“…The experimental procedure was same as described previously by Brodzinsky et al and subsequently used by us , and is briefly given here. The reactions were conducted in 0.15 L Erlenmeyer flasks, open to air, to allow the passage of atmospheric oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…The kinetics was followed by withdrawing the aliquot samples periodically and titrating the unreacted sulfur(IV) iodometrically in slightly acidic medium using sodium thiosulfate as a titrant and starch as an indicator as described earlier . The reproducibility of the replicate measurements was generally ∼10%.…”
Section: Methodsmentioning
confidence: 99%